Influence of air-polishing devices and abrasives on root dentin-an in vitro confocal laser scanning microscope study - Pelka, Matthias; Trautmann, Siegfried; Petschelt, Anselm; Lohbauer, Ulrich (Quintessence International, 2010)
Objective: To assess the influence of air-polishing devices and various abrasives on flat root surfaces. Method and Materials: A total of 168 natural teeth were embedded in polyurethane resin and treated with airborne-particle abrasion using two air-polishing devices (Prophyflex 3, KaVo; EMS Handy, EMS), four abrasives (Airflow powder, EMS; Cleaning powder, KaVo; ClinPro powder, 3M ESPE; and ProphyPearls, KaVo), and three treatment times (5, 10, and 20 seconds). Defects were quantified using a confocal laser scanning microscope. Results: The Prophyflex device clearly generated deeper substance defects compared to the EMS device, regardless of abrasive used (Kruskal-Wallis, P = .004). ProphyPearls abrasive caused the deepest defects with both devices. ClinPro powder produced the least amount of defects. Defect depths increased significantly for all abrasives with increasing treatment times (Kruskal-Wallis, P = .01), and all abrasives except ClinPro powder caused substantial volume loss. Conclusion: The abrasiveness of air-polishing powders differs depending on the polishing device used. ProphyPearls caused more substance loss than ClinPro powder. © 2010 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Airborne-particle abrasion; Glycine powder; Nahco3; Prophypearls; Root defects; Root dentin